2019
DOI: 10.1182/blood-2019-130854
|View full text |Cite
|
Sign up to set email alerts
|

Does Venetoclax Cause Vitiligo?

Abstract: Introduction: Venetoclax is a highly selective, orally bioavailable BCL2 inhibitor which binds to the BH3 domain of BCL2, displacing proapoptotic proteins such as BIM and BAX that once released facilitate induction of apoptosis. Venetoclax is indicated for the treatment of patients with newly-diagnosed acute myeloid leukemia (AML) who are 75 years or older or have other medical conditions that prevent the use of standard chemotherapy. There are many side effects associated with use of venetoclax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…While there have been scattered reports of ‘rash’ and ‘pruritus’ associated with venetoclax therapy, few analyses have included morphological clarification [8]. Isolated case studies have reported venetoclax-associated vitiligo [9,10], panniculitis [11], geographic tongue [12] and disseminated varicella zoster virus [13], respectively. On the other hand, no maculopapular drug eruptions have been described.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been scattered reports of ‘rash’ and ‘pruritus’ associated with venetoclax therapy, few analyses have included morphological clarification [8]. Isolated case studies have reported venetoclax-associated vitiligo [9,10], panniculitis [11], geographic tongue [12] and disseminated varicella zoster virus [13], respectively. On the other hand, no maculopapular drug eruptions have been described.…”
Section: Discussionmentioning
confidence: 99%
“…However, shortly after the drug was re-introduced, she developed vitiligo again. She was treated with topical corticosteroids and kept on venetoclax [19]. In the present case, a decision was made to continue venetoclax and monitor vitiligo closely given the low severity, and the vitiligo not affecting the activities of daily living or causing psychological stress.…”
Section: Discussionmentioning
confidence: 99%